2015
DOI: 10.1530/eje-15-0205
|View full text |Cite
|
Sign up to set email alerts
|

The ARMC5 gene shows extensive genetic variance in primary macronodular adrenocortical hyperplasia

Abstract: Objective Primary macronodular adrenal hyperplasia (PMAH) is a rare type of Cushing’s syndrome (CS) that results in increased cortisol production and bilateral enlargement of the adrenal glands. Recent work showed that the disease may be caused by germline and somatic mutations in the ARMC5 gene, a likely tumor-suppressor gene (TSG). We investigated 20 different adrenal nodules from one patient with PMAH for ARMC5 somatic sequence changes. Design All of the nodules where obtained from a single patient who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 19 publications
1
38
0
1
Order By: Relevance
“…XLAG: All gene carriers develop pituitary disease, 83% adenoma and 17% hyperplasia and all have gigantism [15]. Carney complex: 80% of gene carriers will have biochemical GH abnormality and 10% will manifest clinical acromegaly [16]. A few patient have been described with gigantism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…XLAG: All gene carriers develop pituitary disease, 83% adenoma and 17% hyperplasia and all have gigantism [15]. Carney complex: 80% of gene carriers will have biochemical GH abnormality and 10% will manifest clinical acromegaly [16]. A few patient have been described with gigantism.…”
Section: Introductionmentioning
confidence: 99%
“…Carney complex (CNC) is a syndrome characterized by the presence of acromegaly (10–12%), cardiac and cutaneous myxomas, primary pigmented nodular adrenocortical disease (PPNAD) and pigmented lesions of the skin and mucosae (can vary from lentigines to blue nevi) [16]. CNC presents as familial disease in 70% of the cases and is inherited in an autosomal dominant manner with an overall full penetrance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work identified that PBMAH/MMAD is frequently a genetic disorder, most often due to ARMC5-inactivating mutations, a putative tumor-suppressor gene. Subsequent studies have confirmed the high frequency of ARMC5 mutations in this disorder (43, 44). …”
Section: Genetic Causes Of Cushing Syndrome In Pediatricsmentioning
confidence: 71%
“…In addition to what appeared to be the germline mutation p.Trp476*, sixteen of the 20 nodules harbored a second somatic ARMC5 variant, each of them being unique and specific to one nodule. Allelic losses were identified in two of them (Correa et al 2015).…”
Section: Primary Bilateral Macronodular Adrenal Hyperplasia (Pbmah)mentioning
confidence: 99%